(untitled) (Sophist: Jurnal Sosial Politik Kajian Islam dan Tafsir, 2025)
This study examines the concept of deliberation from the perspective of the Qur’an as a fundamental Islamic principle that is highly relevant to modern social life and decision-making. Deliberation is understood as a process of exchanging opinions between parties to reach the best decision for the common good. The method used is qualitative with a thematic interpretation (maudhu’i) approach, which analyzes Qur’anic verses related to deliberation in various contexts, ranging from family issues to social affairs. The results of the study indicate that deliberation is not only a forum for discussion but also reflects Islamic ethical values such as wisdom, gentleness, and social responsibility. These findings are expected to enrich the body of Islamic scholarship and serve as a practical guide in building social harmony based on Qur’anic values.